(untitled) (Global Journal of Human-Social Science, 2014)
Migration in South East Asia has been happening since a long time and it has indirectly given an impact to the increase of population in countries around the region. Besides population increase, migration of workers has also given an economical impact to the countries in the surrounding region by taking pleasure in certain benefits. The shift in the trend of economic activity from agriculture to industry, and the imbalance in the total population to job opportunities ratio as well as the expansion of education level of a country is often one of the major factors for migration to occur. In the South East Asian region, Malaysia is seen as one of the popular destinations for foreign workers to get a job, especially for those with little or no skills at all. Like other countries, we are rely on foreign workers because of modernization aspect and also the lack of work force in the employment sector. Therefore, the government has introduced a few policies in hiring foreign workers in certain sectors in order to implement economic agendas which have been pre-planned. Even then, their on-going and unstoppable entry has caused the country and its people to worry, especially regarding the threat imposed towards the security of the country.